PC / ABS composite material and preparation method thereof

By using toughening agents and interface enhancers of different particle size ranges in PC/ABS composite materials, a large-size particle size composite effect and microscopic crack network is formed, and the toughness and impact resistance of the material in high temperature, humidity and heat environment is solved, and the problem of the material's toughness and impact resistance is achieved. High toughness and high humidity resistance.

CN119220077APending Publication Date: 2024-12-31GUANGZHOU SHIYUAN ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310803605.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing PC/ABS composite materials have insufficient toughness and impact resistance in high temperature and humidity environments, and cannot meet the requirements of high toughness and humidity resistance.

Method used

Two toughening agents with different particle size ranges (300-700μm and 10-100μm) are used to disperse them in the PC/ABS composite material to form a large-sized particle size composite effect, generate microscopic cracks and hole networks to absorb impact energy, and The toughness and moisture resistance of the material are improved through interface enhancers and acid absorbers.

Benefits of technology

It significantly improves the toughness and impact resistance of PC/ABS composite materials, so that they maintain good mechanical properties in humid and heat environments, and meet the requirements of high toughness and high humidity and heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220077A_ABST
    Figure CN119220077A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to the technical field of new materials, and discloses a PC / ABS composite material and a preparation method thereof.The formula of the PC / ABS composite material comprises, by weight, 60-90 parts of PC resin; 10 to 50 parts of ABS resin; 1 to 20 parts of a flexibilizer; 2, 1 to 10 parts of a flexibilizer; 0.1 to 5 parts of an antioxidant; 0.1 to 5 parts of a lubricant; wherein the particle size range of the flexibilizer 1 is 300-700 [mu] m, and the particle size range of the flexibilizer 2 is 10-100 [mu] m. In the embodiment, two toughening agents with different particle size ranges are adopted and are dispersed in a PC and ABS mixed resin matrix. The toughening agent 1 with the large particle size and the toughening agent 2 with the small particle size can form a large and small particle size compounding effect, micro cracks and holes can be generated to absorb impact energy, and the cracks can be restrained to be in a network shape to reduce macroscopic brittle fracture caused by crack diffusion, so that the toughness of the PC / ABS composite material is improved, and the PC / ABS composite material has good impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of new material technology, and in particular to a PC / ABS composite material and a preparation method thereof. Background Art

[0002] PC / ABS composite material is a thermoplastic plastic blended from polycarbonate (PC) and acrylonitrile-butadiene-styrene copolymer (ABS). It combines the excellent characteristics of two polymer resins. It has the mechanical properties, impact strength and heat resistance of PC resin, and the molding processability of ABS resin. It can be widely used in electronic appliances, mechanical parts, daily necessities, building materials and other fields, and has significant social and economic benefits.

[0003] The electronic and electrical industries all have high toughness requirements for PC / ABS composite materials, so that the products made of PC / ABS composite materials have good impact resistance, can withstand the impact of the external environment, and are strong and durable. In some solutions known to the applicant, a simple toughening agent is added to improve the toughness of the PC / ABS composite material. However, the toughening effect is not satisfactory, especially in a high temperature and hot and humid environment, or when a flame retardant is added, the PC / ABS composite material has poor toughness and impact resistance, and cannot meet the requirements of high toughness and high resistance to heat and humidity. Summary of the invention

[0004] In view of this, some embodiments of the present application provide a PC / ABS composite material and a method for manufacturing the same, so that the PC / ABS composite material has high toughness, that is, has good impact resistance.

[0005] In a first aspect, some embodiments of the present application provide a PC / ABS composite material, wherein the formula of the PC / ABS composite material includes the following components and their contents in parts by weight:

[0006] PC resin, 60-90 parts;

[0007] ABS resin, 10-50 parts;

[0008] Toughener 1, 1-20 parts;

[0009] Toughener 2, 1-10 parts;

[0010] Antioxidant, 0.1-5 parts;

[0011] Lubricant, 0.1-5 parts;

[0012] The particle size of toughening agent 1 is in the range of 300-700 μm, and the particle size of toughening agent 2 is in the range of 10-100 μm.

[0013] In some embodiments, the toughening agent 1 includes an acrylate, MBS or silicon toughening agent; and / or,

[0014] The toughening agent 2 includes acrylate, MBS or silicon-based toughening agents.

[0015] In some embodiments, the PC resin has a melt index (300° C., 1.2 kg) of less than 15 g / 10 min.

[0016] In some embodiments, the PC resin is prepared by phosgene interfacial polycondensation.

[0017] In some embodiments, the ABS resin is a terpolymer obtained by bulk polymerization of acrylonitrile, butadiene and styrene.

[0018] In some embodiments, the formula of the PC / ABS composite material further includes: an acid absorber, 1-5 parts.

[0019] In some embodiments, the acid absorber comprises bicarbonate, vinyl acetate copolymer, or carbodiimide.

[0020] In some embodiments, the formula of the PC / ABS composite material further includes: an interface enhancer, 1-10 parts.

[0021] In some embodiments, the interfacial enhancer includes an ABS resin having an epoxy group branched therein or an AS resin having an epoxy group branched therein.

[0022] In some embodiments, the epoxy group grafting rate is greater than 3%.

[0023] In some embodiments, the formula of the PC / ABS composite material further includes: flame retardant, 1-30 parts.

[0024] In some embodiments, the flame retardant includes phosphorus-nitrogen-based, silicon-based, boron-based halogen-free flame retardants, or phosphazene, phosphate, phosphite, and silicone flame retardants.

[0025] In a second aspect, some embodiments of the present application provide a method for preparing the PC / ABS composite material in the first aspect, comprising:

[0026] According to the formula of PC / ABS composite material, each component is mixed evenly to obtain a premixed material;

[0027] The premixed material is melted and extruded into granules to obtain a PC / ABS composite material.

[0028] In some embodiments, the components are mixed in a mixer using the following mixing parameters:

[0029] The mixture is stirred at a high speed of 1000-2000 rpm for 1-10 min, then stirred at a low speed of 100-500 rpm for 1-5 min, and then the premixed material is output at a speed of 100-300 rpm.

[0030] In some embodiments, extrusion granulation is performed using an extruder at extrusion parameters of a rotation speed of 200-600 rpm and a temperature of 220-280° C.

[0031] In a third aspect, some embodiments of the present application provide a component, at least a portion of which is prepared from the PC / ABS composite material in the first aspect, or at least a portion of the component is prepared from the PC / ABS composite material obtained based on the preparation method in the second aspect.

[0032] In a fourth aspect, some embodiments of the present application provide an electronic product, comprising the component in the third aspect.

[0033] Beneficial effects of the embodiments of the present application: Different from the prior art, the PC / ABS composite material provided in the embodiments of the present application comprises the following components and their weight contents: PC resin, 60-90 parts; ABS resin, 10-50 parts; toughening agent 1, 1-20 parts; toughening agent 2, 1-10 parts; antioxidant, 0.1-5 parts; lubricant, 0.1-5 parts; wherein, the particle size range of toughening agent 1 is 300-700 μm, and the particle size range of toughening agent 2 is 10-100 μm.

[0034] In this embodiment, two tougheners with different particle size ranges are used and dispersed in PC and ABS mixed resin matrices. The large-particle toughener 1 will induce the PC / ABS composite material to produce large holes and cracks under impact force, thereby effectively absorbing the impact energy. The large cracks stop expanding after encountering the small-particle toughener 2, and small holes and cracks are formed near the toughener 2. That is, the small-particle toughener 2 can effectively prevent the large cracks from continuing to expand, so as to avoid macroscopic brittle fractures caused by the continued expansion of the large cracks. Small holes and cracks are interwoven with large holes and cracks to form crack hole networks, and the formation process of these crack hole networks can absorb more impact energy, so that when the PC / ABS composite material is impacted, the impact energy can be effectively absorbed, and the internal microscopic cracks are constrained into a network shape under the action of the toughener 2, reducing the possibility of macroscopic brittle fractures. That is, the large-particle toughening agent 1 and the small-particle toughening agent 2 can form a large-particle size compounding effect, which can not only generate micro cracks and holes to absorb impact energy, but also constrain the cracks to form a network to avoid crack propagation and macro brittle fracture, thereby improving the toughness of the PC / ABS composite material and making it have good impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplified descriptions do not constitute limitations on the embodiments. Elements with the same reference numerals in the drawings represent similar elements, and unless otherwise stated, the figures in the drawings do not constitute proportional limitations.

[0036] Figure 1 Schematic diagram of the process for preparing PC / ABS composite materials in some embodiments of the present application. DETAILED DESCRIPTION

[0037] The present application is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present application, but do not limit the present application in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements can also be made without departing from the concept of the present application. These all belong to the protection scope of the present application.

[0038] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0039] It should be noted that, if there is no conflict, the various features in the embodiments of the present application can be combined with each other, all within the scope of protection of the present application. In addition, although the functional module division is performed in the device schematic diagram and the logical order is shown in the flow chart, in some cases, the steps shown or described can be performed in a sequence different from the module division in the device or the flow chart. In addition, the words "first", "second", "third", etc. used herein do not limit the data and execution order, but only distinguish the same items or similar items with basically the same functions and effects.

[0040] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this specification and in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this specification includes any and all combinations of one or more of the related listed items.

[0041] In addition, the technical features involved in each embodiment of the present application described below can be combined with each other as long as they do not conflict with each other.

[0042] Bisphenol A polycarbonate (PC) is one of the five general engineering plastics, and its usage is second only to polyamide. PC resin is mainly used in the fields of electronics, automobile industry, building materials industry and optical equipment. However, PC resin has a higher price, high processing temperature, large residual stress and poor fluidity. Compared with PC resin, ABS resin has a lower price, excellent performance, and is easy to process and shape, but has poor heat resistance. Blending PC resin and ABS resin can obtain PC / ABS composite materials with good comprehensive performance and high cost performance.

[0043] After the PC / ABS composite materials are modified by toughening, strengthening, flame retardant and filling, their application areas can be further broadened to meet the use needs of more high-performance products. For example, compounding PC / ABS mixed resin and brominated flame retardant can achieve flame retardant modification while sacrificing little toughness of the system. However, brominated flame retardant will produce a lot of smoke and corrosive hydrogen bromide gas during combustion, thus causing secondary hazards.

[0044] At present, halogen-free flame retardant modification is the development trend of flame retardant polymer materials. Due to the differences in flame retardant principles, the amount of flame retardant added and the acid-base properties of the flame retardant itself, the toughness of PC / ABS mixed resin is sacrificed to a greater extent after halogen-free flame retardant modification compared to bromine-based flame retardant modification. In addition, after wet heat treatment, the toughness is further significantly reduced due to the effect of the acidity of the halogen-free flame retardant on the catalytic degradation of PC resin.

[0045] Many plastic structural parts in the electronics and electrical industries require PC / ABS composite materials to be halogen-free flame retardant, have high toughness, be resistant to moisture and heat, and be resistant to high and low temperature cycles. However, after halogen-free flame retardant modification, it is often difficult for PC / ABS composite materials to simultaneously meet the requirements of high toughness and high resistance to moisture and heat.

[0046] In some solutions known to the inventors of the present application, a simple toughening agent is added to improve the toughness of the PC / ABS composite material. However, the toughening effect is not satisfactory, especially in a high temperature and hot and humid environment, or when a flame retardant is added, the PC / ABS composite material has poor toughness and impact resistance, and cannot meet the requirements of high toughness and high resistance to heat and humidity.

[0047] In view of this, some embodiments of the present application provide a PC / ABS composite material, whose formula includes the following components and weight contents: PC resin, 60-90 parts; ABS resin, 10-50 parts; toughening agent 1, 1-20 parts; toughening agent 2, 1-10 parts; antioxidant, 0.1-5 parts; lubricant, 0.1-5 parts; wherein, the particle size range of toughening agent 1 is 300-700μm, and the particle size range of toughening agent 2 is 10-100μm.

[0048] In this embodiment, two tougheners with different particle size ranges are used and dispersed in PC and ABS mixed resin matrices. The large-particle toughener 1 will induce the PC / ABS composite material to produce large holes and cracks under impact force, thereby effectively absorbing the impact energy. The large cracks stop expanding after encountering the small-particle toughener 2, and small holes and cracks are formed near the toughener 2. That is, the small-particle toughener 2 can effectively prevent the large cracks from continuing to expand, so as to avoid macroscopic brittle fractures caused by the continued expansion of the large cracks. Small holes and cracks are interwoven with large holes and cracks to form crack hole networks, and the formation process of these crack hole networks can absorb more impact energy, so that when the PC / ABS composite material is impacted, the impact energy can be effectively absorbed, and the internal microscopic cracks are constrained into a network shape under the action of the toughener 2, reducing the possibility of macroscopic brittle fractures. That is, the large-particle toughening agent 1 and the small-particle toughening agent 2 can form a large-particle size compounding effect, which can not only generate micro cracks and holes to absorb impact energy, but also constrain the cracks to form a network to reduce macro brittle fracture caused by crack propagation, thereby improving the toughness of the PC / ABS composite material and making it have good impact resistance.

[0049] The PC / ABS composite material provided by some embodiments of the present application is described below. The formula of the PC / ABS composite material includes the following components and their weight contents: PC resin, 60-90 parts; ABS resin, 10-50 parts; toughening agent 1, 1-20 parts; toughening agent 2, 1-10 parts; antioxidant, 0.1-5 parts; lubricant, 0.1-5 parts; wherein the particle size range of toughening agent 1 is 300-700 μm, and the particle size range of toughening agent 2 is 10-100 μm.

[0050] In some embodiments, according to the above formula, each component is weighed according to the corresponding weight content and mixed evenly to obtain a premixed material. Then, the premixed material is melted and extruded into granules to obtain a PC / ABS composite material. That is, the PC / ABS composite material is in a granular form. When the structural parts are subsequently produced, the PC / ABS composite material can be injection molded into various shapes by injection molding.

[0051] Among them, PC resin and ABS resin are the main components of PC / ABS composite materials, which makes PC / ABS composite materials have both the mechanical properties, impact strength and heat resistance of PC resin and the molding processability of ABS resin. Compared with conventional PC resin modified materials, PC / ABS composite materials have more advantages in processing and molding, acid and alkali resistance and other chemical reagents, and rigidity and toughness balance.

[0052] The PC resin is bisphenol A polycarbonate. In some embodiments, the PC resin has a melt index (300° C., 1.2 kg) of less than 15 g / 10 min.

[0053] It is understood by those skilled in the art that the melt index is the weight value of the melt of a thermoplastic passing through a standard capillary within 10 minutes under a certain temperature and pressure. The larger the melt index of a PC resin, the lower its viscosity and average molecular weight, the better its processing performance and fluidity. The smaller the melt index of a PC resin, the higher its viscosity and average molecular weight, the worse its processing performance and fluidity.

[0054] In this embodiment, the melt index (300°C, 1.2kg) of the PC resin is less than 15g / 10min, so that the PC resin has a relatively high viscosity and average molecular weight, and a stable molecular structure. There are carbonate bonds in the PC resin that are sensitive to water, which can easily cause molecular chain breakage in a hot and humid environment, resulting in a decrease in its mechanical properties. In this embodiment, the PC resin with a melt index less than 15g / 10min has a stable molecular structure and still has good mechanical properties in a hot and humid environment. Therefore, the PC resin with a melt index less than 15g / 10min is conducive to improving the heat and humidity resistance of the PC / ABS composite material.

[0055] In some embodiments, the PC resin is prepared by phosgene interfacial polycondensation.

[0056] Here, PC resin synthesized by phosgene interfacial polycondensation method is selected to participate in the compounding, such as aromatic polycarbonate, aliphatic polycarbonate or aromatic-aliphatic polycarbonate.

[0057] In this embodiment, the PC resin prepared by the phosgene interfacial polycondensation method has high purity and excellent moisture and heat resistance.

[0058] In some embodiments, the ABS resin is a terpolymer obtained by bulk polymerization of acrylonitrile, butadiene and styrene.

[0059] The bulk method is to directly dissolve polybutadiene rubber in styrene monomer and acrylonitrile for bulk polymerization to obtain ABS resin. The ABS resin prepared by the bulk method has higher purity and lower volatile organic compounds (VOC). After compounding with PC resin, the prepared PC / ABS composite material has better moisture and heat resistance than the PC / ABS composite material including ABS resin prepared by the emulsion method.

[0060] In some embodiments, an ABS resin with a melt index (220°C, 10kg) less than 20g / 10min is selected. It has a relatively high viscosity and average molecular weight, a stable molecular structure, and still has good mechanical properties in a hot and humid environment, which is beneficial to improving the hot and humid resistance of the PC / ABS composite material.

[0061] Wherein, the antioxidant is used to inhibit the degradation reaction of PC resin and ABS resin during the melting process. In some embodiments, the antioxidant includes two types of antioxidants, antioxidant 1 and antioxidant 2. Wherein, the weight part of antioxidant 1 is 0.1-5 parts, and the weight part of antioxidant 2 is 0.1-5 parts. In some embodiments, antioxidant 1 includes hindered phenol antioxidants such as 1010, 1076, and 245, and antioxidant 2 includes phosphite antioxidants such as 168 and PEP36.

[0062] The lubricant is used to reduce the viscosity of the components of the system during the melt blending process, and can also help the PC / ABS composite material to have better demoulding performance during the subsequent injection molding process. In some embodiments, the lubricant can be a polyol ester, silicone, stearic acid, or other lubricant.

[0063] Toughener 1 and toughener 2 are used to increase the toughness of the PC / ABS composite material. It is understood that the PC / ABS composite material here refers to a structural part formed by injection molding of the PC / ABS composite material, such as a plate-shaped or frame-shaped structural part, which has good toughness when subjected to impact force and will not easily undergo brittle fracture.

[0064] Toughener 1 and toughener 2 have different micrometer-level particle size ranges. The particle size range of toughener 1 is 300-700 μm, and the particle size range of toughener 2 is 10-100 μm. That is, the particle size of toughener 1 can be 3-70 times the particle size of toughener 2. In some embodiments, the particle size range of toughener 1 is much larger than the particle size range of toughener 2.

[0065] During the melt granulation process, tougheners 1 and 2 will not be melted and will be distributed in the PC and ABS mixed resin system. During granulation, the large-sized toughener 1 may be sheared into particles with a smaller particle size. That is, tougheners 1 and 2 still exist as particles in the PC / ABS composite material and are wrapped in the mixed resin. When the PC / ABS composite material is injection molded, tougheners 1 and 2 will still not be fused, but will be evenly distributed in the injection-molded structural parts as particles.

[0066] It can be understood by those skilled in the art that toughness means the ability of a material to absorb energy before actual fracture or destruction occurs. The better the toughness, the less likely it is that brittle fracture will occur. The toughening mechanism of toughener 1 and toughener 2 is that the large-particle-size toughener 1 will induce large holes and cracks in the PC / ABS composite material under impact force, thereby effectively absorbing impact energy. The large cracks stop expanding after encountering the small-particle-size toughener 2, and small holes and cracks are formed near the toughener 2. That is, the small-particle-size toughener 2 can effectively prevent the large cracks from continuing to expand, so as to avoid macroscopic brittle fractures caused by the continued expansion of the large cracks. Small holes and cracks are interwoven with large holes and cracks to form crack hole networks, and the formation process of these crack hole networks can absorb more impact energy, so that when the PC / ABS composite material is impacted, the impact energy can be effectively absorbed, and the internal microscopic cracks are constrained into a network shape under the action of the toughener 2, reducing the possibility of macroscopic brittle fractures.

[0067] That is, the large-particle toughening agent 1 and the small-particle toughening agent 2 can form a large-particle size compounding effect, which can not only generate micro cracks and holes to absorb impact energy, but also constrain the cracks to form a network to reduce macro brittle fracture caused by crack propagation, thereby improving the toughness of the PC / ABS composite material and making it have good impact resistance.

[0068] In some embodiments, the toughening agent 1 includes an acrylate-based, MBS resin-based, or silicon-based toughening agent.

[0069] Acrylate is a general term for acrylic acid and its homologues. Acrylate toughening agents are particles formed by granulation of acrylic acid. For example, toughening agent 1 can be methyl acrylate particles or ethyl acrylate particles. MBS resin is a terpolymer of methyl methacrylate (M), butadiene (B) and styrene (S). MBS resin toughening agents are particles formed by granulation of MBS resin. For example, toughening agent 1 can be particles formed by granulation of MBS resin. Silicone toughening agents can be silicone particles. For example, toughening agent 1 can be silicone particles.

[0070] In some embodiments, toughener 2 includes acrylate, MBS or silicon toughener. That is, toughener 2 and toughener 1 are made of the same material, but with different particle size ranges. For example, toughener 2 can be methyl acrylate particles or ethyl acrylate particles. For example, toughener 2 can be particles formed by granulation of MBS resin. For another example, toughener 2 can be silicone particles.

[0071] In some embodiments, the formula of the PC / ABS composite material further includes: an acid absorber, 1-5 parts. It is understandable that when the PC resin and the ABS resin are melt-mixed, acidic components such as carboxyl groups are generated. The acidic components easily catalyze the degradation of the PC resin and affect the toughness of the PC / ABS composite material. Therefore, by adding an acid absorber, the acidic components are neutralized and the effect of the acidic components on the toughness is reduced.

[0072] In some embodiments, the acid absorber includes bicarbonate, vinyl acetate copolymer or carbodiimide. For example, the formula includes 1-5 parts of bicarbonate. In this embodiment, the acid absorber is not melted in the molten PC / ABS mixed resin and is evenly distributed in the resin system.

[0073] In this embodiment, by adding 1-5 parts of acid absorber into the formula, it can react with the carboxyl group, thereby consuming the acid components generated in the system, which is beneficial for the PC / ABS composite material to maintain a high toughness and is beneficial for the PC / ABS composite material to have excellent moisture and heat resistance.

[0074] In some embodiments, the formula of the PC / ABS composite material further includes: an interface enhancer, 1-10 parts.

[0075] Here, the interface enhancer is an auxiliary agent for improving the interface strength between the PC resin and the ABS resin. In some embodiments, the interface enhancer includes an ABS resin with an epoxy group or an AS resin with an epoxy group. It is understood by those skilled in the art that the ABS resin is a terpolymer obtained from acrylonitrile, butadiene and styrene, and the AS resin is a styrene-acrylonitrile copolymer. It is understood that the interface enhancer will not be melted in the molten PC / ABS mixed resin and is evenly distributed in the resin system.

[0076] In order to act as an interface enhancer, ABS resin or AS resin is grafted with epoxy groups. In some embodiments, the grafting rate of epoxy groups is greater than 3%, which is conducive to the interface enhancer to play a good interface enhancement role, and is beneficial for the PC / ABS composite material to still have high toughness in a hot and humid environment, that is, it has excellent hot and humid resistance.

[0077] In some embodiments, the formula of the PC / ABS composite material further includes: flame retardant, 1-30 parts.

[0078] Here, the flame retardant is an auxiliary agent used to improve the flame retardant properties of the PC / / ABS composite material. In some embodiments, the flame retardant includes phosphorus nitrogen series, silicon series, boron series halogen-free flame retardant, or phosphazene, phosphate, phosphite, silicone flame retardant.

[0079] In this embodiment, by adding 1-30 parts of flame retardant, the structural part formed by injection molding of PC / / ABS composite material has good flame retardant performance.

[0080] In summary, by designing a formula with the above components and weight contents, on the one hand, the large-particle toughening agent 1 and the small-particle toughening agent 2 can form a large-particle size compounding effect, which can not only generate micro cracks and holes to absorb impact energy, but also constrain the cracks to be network-shaped to reduce macro brittle fractures caused by crack propagation, thereby improving the toughness of the PC / ABS composite material and making it have good impact resistance. On the other hand, the PC / ABS composite material still has high toughness in a hot and humid environment, that is, it has excellent hot and humid resistance. In addition, it also has good flame retardant properties, meeting the requirements of high toughness and high hot and humid resistance.

[0081] Some embodiments of the present application also provide a method for preparing a PC / ABS composite material, such as Figure 1 As shown, the method S100 includes:

[0082] S10: According to the formula of the PC / ABS composite material, the components are mixed uniformly to obtain a premixed material.

[0083] S20: After the premixed material is melted, it is extruded and granulated to obtain a PC / ABS composite material.

[0084] The formula of the PC / ABS composite material can be any one of the above embodiments. In some embodiments, the formula includes the following components and weight percentages: PC resin, 60-90 parts; ABS resin, 10-50 parts; toughening agent 1, 1-20 parts; toughening agent 2, 1-10 parts; antioxidant, 0.1-5 parts; lubricant, 0.1-5 parts; wherein the particle size of toughening agent 1 is in the range of 300-700 μm, and the particle size of toughening agent 2 is in the range of 10-100 μm.

[0085] In some embodiments, the formula further comprises: an acid absorber, 1-5 parts. In some embodiments, the formula further comprises: an interface enhancer, 1-10 parts. In some embodiments, the formula further comprises: a flame retardant, 1-30 parts.

[0086] Since this formula is the same as the formula in any of the above embodiments, please refer to the description in the above embodiments for the function of each component and the performance brought to the PC / ABS composite material, which will not be repeated here.

[0087] In some embodiments, each component in the formula is weighed according to the corresponding weight portion and put into a mixer for mixing. During mixing, the following mixing parameters can be used: high-speed stirring at a speed of 1000-2000 rpm for 1-10 minutes, followed by low-speed stirring at a speed of 100-500 rpm for 1-5 minutes, and then outputting the premixed material at 100-300 rpm. Under this mixing parameter, each component can be mixed evenly and give full play to their respective properties, such as the toughening performance of the toughening agent, the anti-degradation performance of the antioxidant, the neutralization performance of the acid absorber, the interface strengthening performance of the interface enhancer, and the flame retardant performance of the flame retardant. Thus, the uniformly mixed premixed material is conducive to the preparation of the above-mentioned PC / ABS composite material with good performance in all aspects and uniformity.

[0088] In some embodiments, the premixed material is put into an extruder, and the extrusion parameters are set to a rotation speed of 200-600 rpm and a temperature of 220-280° C. Under the extrusion parameters, the PC resin, ABS resin and antioxidant are melted, and then the toughening agent 1, the toughening agent 2, the interfacial enhancer and the acid absorber are wrapped, extruded, sheared, and solidified into granules.

[0089] In summary, the PC / ABS composite material prepared by the above method has high toughness, good impact resistance, and good flame retardant properties, and can meet the requirements of high toughness and high moisture and heat resistance.

[0090] Some embodiments of the present application further provide a component, at least a portion of which is prepared from the PC / ABS composite material in any one of the above embodiments, or at least a portion of the component is prepared from the PC / ABS composite material obtained by the preparation method in any one of the above embodiments.

[0091] In some embodiments, the component may be a housing or frame of an electronic product, etc. For example, when the electronic product is an educational robot, the component may be a housing or frame of the educational robot.

[0092] In this embodiment, the component has the properties of the above-mentioned PC / ABS composite material. Specifically, the component has high toughness, good impact resistance, and good flame retardant properties, and can meet the requirements of high toughness and high moisture and heat resistance.

[0093] Some embodiments of the present application further provide an electronic product, including the components in the above embodiments. Thus, the electronic product has the structure and function of the components in the above embodiments, which will not be described one by one here.

[0094] In order to further illustrate the technical solution of the present application, several examples and comparative examples of the prepared PC / ABS composite materials are provided below for verification purposes.

[0095] Embodiment 1:

[0096] Weigh materials: Weigh each component according to implementation formula 1#, which includes the following components and weight contents:

[0097] 60 parts of PC resin polymerized by phosgene interfacial polycondensation;

[0098] ABS resin polymerized by bulk method, 10 parts;

[0099] 1.5 parts of MBS toughening agent with a particle size distribution of 300-500 μm;

[0100] 2.2 parts of MBS toughening agent with a particle size distribution of 50-100 μm;

[0101] Flame retardant (BDP), 10 parts;

[0102] Interface enhancer (ABS-GMA, grafting rate 5%), 2 parts;

[0103] Acid absorbent (sodium bicarbonate), 1 part;

[0104] Antioxidant 1 (1076), 0.2 parts;

[0105] Antioxidant 2 (168), 0.31 parts;

[0106] Lubricant (stearate), 1 part.

[0107] Mixing material: Each component in the above-mentioned implementation formula 1# is added into a mixer according to the corresponding weight to mix uniformly to obtain a premixed material. The following mixing parameters are adopted: first, high-speed stirring at a speed of 1000 rpm for 6 minutes, then low-speed stirring at a speed of 20 rpm for 3 minutes, and the uniformly mixed material is discharged at 100 rpm.

[0108] Extrusion granulation: The premixed materials are melt-blended and extruded through a twin-screw extruder to obtain a PC / ABS composite material (granular). The following extrusion parameters are used: the main engine speed of the twin-screw extruder is 350 rpm, and the temperature of each zone is controlled within the temperature range of 240 to 260°C.

[0109] Preparation of test specimens: A certain amount of PC / ABS composite material is made into a specimen through injection molding. The dimensions of the test specimen meet the dimensions specified in the ISO notched impact test standard, such as 80±2mm in length, 10±0.2mm in width, and 4±0.2mm in thickness.

[0110] Embodiment 2:

[0111] The difference from Example 1 is that the implementation formula 2# includes the following components and contents by weight:

[0112] 70 parts of PC resin polymerized by phosgene interfacial polycondensation;

[0113] ABS resin polymerized by bulk method, 20 parts;

[0114] 1.8 parts of MBS toughening agent with a particle size distribution of 300-500 μm;

[0115] 2, 3 parts of MBS toughening agent with a particle size distribution of 50-100 μm;

[0116] Flame retardant (BDP), 15 parts;

[0117] Interface enhancer (ABS-GMA, grafting rate 5%), 5 parts;

[0118] Acid absorbent (sodium bicarbonate), 3 parts;

[0119] Antioxidant 1 (1076), 1 part;

[0120] Antioxidant 2 (168), 2 parts;

[0121] Lubricant (stearate), 4 parts.

[0122] Embodiment 3:

[0123] The difference from Example 1 is that the implementation formula 3# includes the following components and contents by weight:

[0124] 80 parts of PC resin polymerized by phosgene interfacial polycondensation;

[0125] ABS resin polymerized by bulk method, 40 parts;

[0126] 10 parts of MBS toughening agent with a particle size distribution of 300-500 μm;

[0127] 2.6 parts of MBS toughening agent with a particle size distribution of 50-100 μm;

[0128] Flame retardant (BDP), 18 parts;

[0129] Interface enhancer (ABS-GMA, grafting rate 5%), 7 parts;

[0130] Acid absorbent (sodium bicarbonate), 5 parts;

[0131] Antioxidant 1 (1076), 2 parts;

[0132] Antioxidant 2 (168), 0.8 parts;

[0133] Lubricant (stearate), 2 parts.

[0134] Embodiment 4:

[0135] The difference from Example 1 is that the implementation formula 4# includes the following components and contents by weight:

[0136] 90 parts of PC resin polymerized by phosgene interfacial polycondensation;

[0137] ABS resin polymerized by bulk method, 30 parts;

[0138] 1.15 parts of MBS toughening agent with a particle size distribution of 300-500 μm;

[0139] 2.10 parts of MBS toughening agent with a particle size distribution of 50-100 μm;

[0140] Flame retardant (BDP), 25 parts;

[0141] Interface enhancer (ABS-GMA, grafting rate 5%), 9 parts;

[0142] Acid absorbent (sodium bicarbonate), 4 parts;

[0143] Antioxidant 1 (1076), 3 parts;

[0144] Antioxidant 2 (168), 1 part;

[0145] Lubricant (stearate), 5 parts.

[0146] Comparative Example 1:

[0147] The difference from Example 1 is that the comparative formula 1# includes the following components and contents in parts by weight:

[0148] 60 parts of PC resin polymerized by phosgene interfacial polycondensation;

[0149] ABS resin polymerized by bulk method, 10 parts;

[0150] 1.7 parts of MBS toughening agent with a particle size distribution of 300-500 μm;

[0151] 2.0 parts of MBS toughening agent with a particle size distribution of 50-100 μm;

[0152] Flame retardant (BDP), 10 parts;

[0153] Interface enhancer (ABS-GMA, grafting rate 5%), 2 parts;

[0154] Acid absorbent (sodium bicarbonate), 1 part;

[0155] Antioxidant 1 (1076), 0.2 parts;

[0156] Antioxidant 2 (168), 0.3 parts;

[0157] Lubricant (stearate), 1 part.

[0158] Comparative Example 2:

[0159] The difference from Example 1 is that the comparative formula 2# includes the following components and contents in parts by weight:

[0160] 60 parts of PC resin polymerized by phosgene interfacial polycondensation;

[0161] ABS resin polymerized by bulk method, 10 parts;

[0162] 1.0 parts of MBS toughening agent with a particle size distribution of 300-500 μm;

[0163] 2.7 parts of MBS toughening agent with a particle size distribution of 50-100 μm;

[0164] Flame retardant (BDP), 10 parts;

[0165] Interface enhancer (ABS-GMA, grafting rate 5%), 2 parts;

[0166] Acid absorbent (sodium bicarbonate), 1 part;

[0167] Antioxidant 1 (1076), 0.2 parts;

[0168] Antioxidant 2 (168), 0.3 parts;

[0169] Lubricant (stearate), 1 part.

[0170] Comparative Example 3:

[0171] The difference from Example 1 is that the comparative formula 3# includes the following components and contents in parts by weight:

[0172] 60 parts of PC resin polymerized by phosgene interfacial polycondensation;

[0173] ABS resin polymerized by bulk method, 10 parts;

[0174] 1.5 parts of MBS toughening agent with a particle size distribution of 300-500 μm;

[0175] 2.2 parts of MBS toughening agent with a particle size distribution of 50-100 μm;

[0176] Flame retardant (BDP), 10 parts;

[0177] Interface enhancer (ABS-GMA, grafting rate 5%), 0 parts;

[0178] Acid absorbent (sodium bicarbonate), 1 part;

[0179] Antioxidant 1 (1076), 0.2 parts;

[0180] Antioxidant 2 (168), 0.3 parts;

[0181] Lubricant (stearate), 1 part.

[0182] Comparative Example 4:

[0183] The difference from Example 1 is that the comparative formula 4# includes the following components and contents in parts by weight:

[0184] 60 parts of PC resin polymerized by phosgene interfacial polycondensation;

[0185] ABS resin polymerized by bulk method, 10 parts;

[0186] 1.5 parts of MBS toughening agent with a particle size distribution of 300-500 μm;

[0187] MBS toughening agent with a particle size distribution of 50-100 μm, 2 parts; flame retardant (BDP), 10 parts;

[0188] Interface enhancer (ABS-GMA, grafting rate 5%), 2 parts;

[0189] Acid absorbent (sodium bicarbonate), 0 parts;

[0190] Antioxidant 1 (1076), 0.2 parts;

[0191] Antioxidant 2 (168), 0.3 parts;

[0192] Lubricant (stearate), 1 part.

[0193] In summary, the formulas of Examples 1-4 and Comparative Examples 1-4 are shown in Table 1 below:

[0194] Table 1 Recipe

[0195]

[0196]

[0197] Some test specimens corresponding to Examples 1-4 and Comparative Examples 1-4 in Table 1 were subjected to an Izod impact test according to ISO-180 standard to obtain the initial ISO impact strength of each Example and each Comparative Example.

[0198] Some test specimens corresponding to Examples 1-4 and Comparative Examples 1-4 in Table 1 were subjected to flame retardancy tests according to ISO 4589-2 standard to obtain the vertical combustion fire rating of each Example and each Comparative Example.

[0199] After treating some test specimens corresponding to Examples 1-4 and Comparative Examples 1-4 in Table 1 at a humidity of 85% and a temperature of 85°C for 120 hours, an Izod impact test was performed according to ISO-180 standard to obtain the ISO impact strength of each Example and each Comparative Example after wet heat treatment.

[0200] Some test specimens corresponding to Examples 1-4 and Comparative Examples 1-4 in Table 1 were treated at a humidity of 85% and a temperature of 85°C for 120 hours, and then subjected to a flame retardancy test according to ISO 4589-2 standard to obtain the vertical combustion fire retardancy rating of each Example and each Comparative Example after wet heat treatment.

[0201] The measurement results of the above Examples 1-4 and Comparative Examples 1-4 are shown in Table 2 below:

[0202] Table 2 Measurement results

[0203]

[0204]

[0205] As can be seen from Table 2, the test specimens (PC / ABS composite materials) prepared in Examples 1-4 exhibited good impact properties (toughness), moisture and heat resistance, and flame retardancy. Specifically, the initial ISO notched impact strength reached 70 kJ / m 2 Above; after 85% and 85℃ wet heat treatment, the impact strength can still be maintained at 40kJ / m 2 Above; before and after 85%, 85℃ wet heat treatment, the flame retardant grade is 1.5mm, V-0.

[0206] Compared with Example 1, the components of Comparative Example 1 do not contain the toughening agent 2 (MBS-2) with a small particle size range, and its initial ISO notched impact strength is 63 kJ / m 2 , 85%, 85℃ after wet heat treatment, the impact strength dropped to 32kJ / m 2 The toughness and moisture and heat resistance are not ideal. This is because the lack of toughener 2 cannot form a particle size compounding effect with the toughener 1 (MBS-1) with a large particle size range. The large cracks generated by toughener 1 spread freely, which easily leads to macroscopic brittle fracture.

[0207] Compared with Example 1, the components of Comparative Example 2 do not contain the toughening agent 1 (MBS-1) with a large particle size range, and its initial ISO notched impact strength is only 45 kJ / m 2, 85%, 85℃ after wet heat treatment, the impact strength dropped to 23kJ / m 2 , the toughness and moisture and heat resistance are not ideal. It can be seen that the toughness and moisture and heat resistance of Comparative Example 2 are lower than those of Comparative Example 1. This is because, compared with the toughening agent 1 in a large particle size range, the toughening agent 2 in a small particle size range has limited effect in inducing the generation of cavities and cracks under the action of impact force, and the toughening effect is not ideal.

[0208] Compared with Example 1, Comparative Example 3 did not add an interface enhancer, resulting in insufficient interface strength between PC resin and ABS resin, and its initial strength was 58 kJ / m 2 , 85%, 85℃ after wet heat treatment, the impact strength dropped to 29kJ / m 2 .

[0209] Compared with Example 1, Comparative Example 4 did not add an acid absorber, and the initial impact strength reached 65 kJ / m 2 , 85%, 85℃ after wet heat treatment, the impact strength dropped significantly to 20kJ / m 2 , and the flame retardant grade also dropped to V-2. Without the addition of an acid absorber, the carboxyl groups generated by the flame retardant (BDP) during the 85% and 85°C wet heat treatment cannot be effectively neutralized, so the carboxyl groups easily catalyze the degradation of PC resin. Therefore, while the impact strength dropped significantly, the flame retardant grade also dropped significantly.

[0210] In summary, some embodiments of the present application provide a PC / ABS composite material and a preparation method thereof, wherein the formula includes the following components and their weight contents: PC resin, 60-90 parts; ABS resin, 10-50 parts; toughening agent 1, 1-20 parts; toughening agent 2, 1-10 parts; antioxidant, 0.1-5 parts; lubricant, 0.1-5 parts; wherein the particle size range of toughening agent 1 is 300-700 μm, and the particle size range of toughening agent 2 is 10-100 μm.

[0211] In this embodiment, by designing the formula in the above-mentioned embodiments 1-4, on the one hand, the large-particle-size toughening agent 1 and the small-particle-size toughening agent 2 can form a large-particle-size compounding effect, which can generate micro cracks and holes to absorb impact energy, and can constrain the cracks to be in a network shape to reduce macro brittle fractures caused by crack diffusion, thereby improving the toughness of the PC / ABS composite material and making it have good impact resistance. On the other hand, the PC / ABS composite material still has high toughness in a hot and humid environment, that is, it has excellent hot and humid resistance. In addition, it also has good flame retardant properties, meeting the requirements of high toughness and high hot and humid resistance.

[0212] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Under the concept of the present application, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present application as described above, which are not provided in detail for the sake of simplicity. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features can be replaced by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A PC / ABS composite material, characterized in that: The formula of the PC / ABS composite material includes the following components and contents by weight: PC resin, 60-90 parts; ABS resin, 10-50 parts; Toughener 1, 1-20 parts; Toughener 2, 1-10 parts; Antioxidant, 0.1-5 parts; Lubricant, 0.1-5 parts; The particle size of toughening agent 1 is in the range of 300-700 μm, and the particle size of toughening agent 2 is in the range of 10-100 μm.

2. The PC / ABS composite material according to claim 1, characterized in that: The toughening agent 1 includes acrylate, MBS or silicon toughening agents; and / or, The toughening agent 2 includes acrylate, MBS or silicon toughening agents.

3. The PC / ABS composite material according to claim 1, characterized in that: The PC resin has a melt index (300° C., 1.2 kg) of less than 15 g / 10 min.

4. The PC / ABS composite material according to claim 3, characterized in that: The PC resin is prepared by phosgene interfacial polycondensation method.

5. The PC / ABS composite material according to claim 1, characterized in that: The ABS resin is a terpolymer obtained by polymerizing acrylonitrile, butadiene and styrene by a bulk process.

6. The PC / ABS composite material according to any one of claims 1 to 5, characterized in that: The formula of the PC / ABS composite material also includes: Acid absorbent, 1-5 parts.

7. The PC / ABS composite material according to claim 6, characterized in that: The acid absorbent includes bicarbonate, vinyl acetate copolymer or carbodiimide.

8. The PC / ABS composite material according to any one of claims 1 to 5, characterized in that: The formula of the PC / ABS composite material also includes: Interface enhancer, 1-10 parts.

9. The PC / ABS composite material according to claim 8, characterized in that: The interface enhancer includes ABS resin with epoxy groups branched or AS resin with epoxy groups branched.

10. The PC / ABS composite material according to claim 9, characterized in that: The branching rate of the epoxy groups is greater than 3%.

11. The PC / ABS composite material according to any one of claims 1 to 5, characterized in that: The formula of the PC / ABS composite material also includes: Flame retardant, 1-30 parts.

12. The PC / ABS composite material according to claim 11, characterized in that: The flame retardant includes phosphorus-nitrogen series, silicon series, boron series halogen-free flame retardant, or phosphazene, phosphate, phosphite, and organosilicon flame retardant.

13. A method for preparing the PC / ABS composite material according to any one of claims 1 to 12, characterized in that: include: According to the formula of the PC / ABS composite material, the components are mixed evenly to obtain a premixed material; The premixed material is melted and then extruded and granulated to obtain the PC / ABS composite material.

14. The preparation method according to claim 13, characterized in that: The components are mixed in a mixer using the following mixing parameters: The mixture is stirred at a high speed of 1000 to 2000 rpm for 1 to 10 minutes, and then stirred at a low speed of 100 to 500 rpm for 1 to 5 minutes, and then the premixed material is output at a speed of 100 to 300 rpm.

15. The preparation method according to claim 13, characterized in that: The extrusion granulation is carried out by using an extruder at extrusion parameters of a rotation speed of 200-600 rpm and a temperature of 220-280°C.

16. A component, characterized in that At least a portion of the component is prepared from the PC / ABS composite material according to any one of claims 1 to 12, or at least a portion of the component is prepared from the PC / ABS composite material obtained by the preparation method according to any one of claims 13 to 15.

17. An electronic product, characterized in that: Comprising the component as claimed in claim 16.